2019
DOI: 10.1038/s41598-019-39239-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated single-base resolution maps of transcriptome, sRNAome and methylome of Tomato yellow leaf curl virus (TYLCV) in tomato

Abstract: Geminiviruses are plant ssDNA viruses that replicate through dsDNA intermediates and form minichromosomes which carry the same epigenetic marks as the host chromatin. During the infection, geminiviruses are targets of the post-transcriptional and transcriptional gene silencing machinery. To obtain insights into the connection between virus-derived small RNAs (vsRNAs), viral genome methylation and gene expression, we obtained the transcriptome, sRNAome and methylome from the geminivirus Tomato yello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 72 publications
(97 reference statements)
9
37
1
Order By: Relevance
“…In light of the role of AGO4 in RdDM and to directly assess the impact of V2 and AGO4 on the methyl-state of the viral DNA, we used bisulfite sequencing (BS-seq) to measure DNA methylation of the intergenic region (IR) of the viral genome, which presents the highest methylation levels during the infection ( Piedra-Aguilera et al, 2019 ). As shown in Figure 4A , cytosine methylation in this region in all contexts (CG, CHG, and CHH) was almost undetectable in the wild-type viral genome in local infections at 3 or 9 days post-inoculation (dpi), while it reached ~60% and~80%, respectively, in the V2 null mutant ( Figure 4A ; Figure 4—figure supplement 1A ; Supplementary file 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In light of the role of AGO4 in RdDM and to directly assess the impact of V2 and AGO4 on the methyl-state of the viral DNA, we used bisulfite sequencing (BS-seq) to measure DNA methylation of the intergenic region (IR) of the viral genome, which presents the highest methylation levels during the infection ( Piedra-Aguilera et al, 2019 ). As shown in Figure 4A , cytosine methylation in this region in all contexts (CG, CHG, and CHH) was almost undetectable in the wild-type viral genome in local infections at 3 or 9 days post-inoculation (dpi), while it reached ~60% and~80%, respectively, in the V2 null mutant ( Figure 4A ; Figure 4—figure supplement 1A ; Supplementary file 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, reduced representation bisulfite sequencing (RRBS) of cucumber mosaic virus (CMV)-infected Nicotiana tabacum revealed that DMRs are enriched within CHH sequence contexts and are mainly located on the gene body [34]. Deep sequencing of bisulfite-treated DNA (BS-Seq) on TYLCV-infected tomato identify different epigenetic scenarios in the viral genome, suggesting that DNA methylation plays roles in plant defense and viral gene regulation [43]. Currently, whole-genome bisulfite sequencing (WGBS) has emerged as a powerful approach for studying DNA methylation by providing genome-wide methylation profiles at single-base resolution [44].…”
Section: Introductionmentioning
confidence: 99%
“…However, technological advancements have made it feasible to identify methylomes at a single-base resolution using BS-seq in soybean [248]. Methylome profiles studied among diverse accessions in key crop species including chickpea and soybean showed thousands of differentially methylated regions (DMRs) [248,249,250]. Genome-wide cytosine methylation analysis has been done on soybean for roots, stems, leaves, and cotyledons of developing seeds at single-base resolution.…”
Section: Omics-based Breeding Approaches For Adaptive Traits In Pumentioning
confidence: 99%